Zeitgeist becomes form : German fashion photography 1945-1995 - Gundlach, F.C.; Honnef, Klaus; Kaufhold, Enno ([Stuttgart] : Institut für Auslandsbeziehungen, 1995)
Rohrbah, Charlotte ; Leonard, Norbert ; Maywald, Willy ; Relang, Regi ; Flöter, Hubs ; Tobias, Herbert ; McBride, Will ; March, Charlotte ; Gundlach, F.C. ; von Alvensleben, Christian ; Vormwald, Gerhard ; Newton, Helmut ; Ommer, Uwe ; Schumacher, Jacques ; Puhlmann, Rico ; Knaup, Peter ; Brehm, Heribert ; Rau, André ; Bergemann, Sibylle ; Wackerbarth, Horst ; von Renner, Ivo ; etc.
Zeitgeist becomes form : German Fashion Photography : 1945-1995, An exhibition by the Institute for Foreign Cultural Relations
boek